2008
DOI: 10.1175/2008jcli1876.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent Changes in Downward Longwave Radiation at King Sejong Station, Antarctica

Abstract: Effects of cloud, air temperature, and specific humidity on downward longwave irradiance and their long-term variabilities are examined by analyzing the measurements made at the King Sejong Station in the Antarctic Peninsula during the period of 1996-2006. It has been shown that the downward longwave irradiance (DLR) is significantly correlated with three variables: air temperature, specific humidity, and cloudiness. Based on the relationship of the three variables with DLR, a multiple linear regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…In terms of the UV radiation related to the stratospheric ozone depletion, this station is located in the range of polar vortex area and thus largely affected by the Antarctic ozone hole during the austral springtime. Compared to other Antarctic inland stations, the King Sejong Station shows relatively warmer and more humid air conditions (Cho et al, 2008), and more frequent cloud condition compared to the Antarctic inland (Choi et al, 2008), thereby revealing the characteristics of an oceanic climate better. The climatology of local meteorological pattern (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) is as in the following: − 1.6°C for the surface temperature, 8.0 m/s for the surface wind speed, 89% for the relative humidity, and 6.7 oktas for cloud fraction.…”
Section: Data Description and Methodologymentioning
confidence: 91%
“…In terms of the UV radiation related to the stratospheric ozone depletion, this station is located in the range of polar vortex area and thus largely affected by the Antarctic ozone hole during the austral springtime. Compared to other Antarctic inland stations, the King Sejong Station shows relatively warmer and more humid air conditions (Cho et al, 2008), and more frequent cloud condition compared to the Antarctic inland (Choi et al, 2008), thereby revealing the characteristics of an oceanic climate better. The climatology of local meteorological pattern (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) is as in the following: − 1.6°C for the surface temperature, 8.0 m/s for the surface wind speed, 89% for the relative humidity, and 6.7 oktas for cloud fraction.…”
Section: Data Description and Methodologymentioning
confidence: 91%
“…The increase in cloud-free DLR was mainly related to the corresponding temperature increase. On the other hand, it has been shown that the all-sky DLR is also strongly related to regional temperature, humidity and cloudiness effects which can even result in a negative trend despite rising greenhouse gas concentrations [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the objective of this study is to evaluate spatio-temporal patterns in KT over a recent time period together with long-term trends in KT in Korea. Using a multiple regression model for KT, we also estimate the individual contributions of several atmospheric parameters influencing KT [30].…”
Section: Methodsmentioning
confidence: 99%
“…We also conducted multiple linear regressions and analyzed partial correlation coefficients in order to estimate the individual contributions of the parameters influencing K T [30]. Table 1.…”
Section: Clearness Indexmentioning
confidence: 99%
See 1 more Smart Citation